Comparison of Endocrine Profile and In Vitro Fertilization Outcome in Patients with PCOS, Ovulatory PCO, or Normal Ovaries - Yi-Ping Zhong; Ying Ying; Hai-Tao Wu; Can-Quan Zhou; Yan-Wen Xu; Qiong Wang; Jie Li; Xiao-Ting Shen; Jin Li (International Journal of Endocrinology)
Aim. To compare the basic endocrine profile and outcomes of in vitro fertilization (IVF) in women with polycystic ovary syndrome (PCOS), ovulatory polycystic ovaries (PCO), or normal ovaries (NO). Methods. The basic clinical features and in vitro fertilization and embryo transfer outcome in patients receiving IVF or intracytoplasmic sperm injection (ICSI) were retrospectively analyzed. Results. The body mass index, basal luteinizing hormone, and testosterone levels were significantly lower in patients with ovulatory PCO compared to those in patients with PCOS. The PCOS patients exhibited the shortest duration of ovarian stimulation and lowest dose of gonadotropin, followed by the ovulatory PCO and NO patients. The ovulatory PCO and PCOS patients showed similar levels of E2 on the human chorionic gonadotropin treatment day and numbers of oocytes, which were both significantly higher than those of the NO patients. The fertilization rate of the PCOS patients was significantly lower than the other two groups. Compared to NO patients, the cleavage rate was lower in both PCOS and ovulatory PCO patients, however, the number of available embryos was significantly more in these two groups. The incidence of the moderate to severe ovarian hyperstimulation syndrome (OHSS) was markedly higher in the PCOS and ovulatory PCO patients. Conclusion. Ovulatory PCO patients do not express similar endocrine abnormalities as PCOS patients. Although the fertilization rate and cleavage rate were relatively low in PCOS patients, ultimately, all the three groups showed similar transferred embryo numbers, clinical pregnancy rates, and implantation rates. Since the incidence of OHSS was much higher in the PCOS and ovulatory PCO patients, we should take more care of these patients and try to prevent severe OHSS.